WACANA KAMPANYE POLITIK DALAM BALIHO DAN SPANDUK PEMILIHAN GUBERNUR – WAKIL GUBERNUR BALI TAHUN 2013 DAN PEMILIHAN LEGISLATIF DI BALI TAHUN 2014 : KAJIAN PRAGMATIK - Olivia Dita Kesari, Dewa Ayu Made (Humanis; Volume 9. No. 3. Desember 2014)
This study aims to analyze and understand the discourse of political campaign in election. Billboards and banners of political campaign in election is used as an object of research. The object of research was analyzed by using speech act theory, illocutionary speech act theory, and implicature theory. In terms of the speech act found speech acts of direct and indirect. In terms of the illocutionary speech act found assertive, directive, commissive, and expressive speech act. Then, in terms of the implicature, the discourse of political campaign aims to convince civil society to choose them.
Keywords: speech act, illocutionary speech act, and implicature.